The Making of Modern Psychiatry - Chase, Ronald (Logos Verlag Berlin, 2018)
The field of psychiatry changed dramatically in the latter half of the nineteenth century, largely by embracing science. The transformation was most evident in Germany, where many psychiatrists began to work concurrently in the clinic and the laboratory. Some researchers sought to discover brain correlates of mental illness, while others looked to experimental psychology for insights into mental dynamics. Featured here, are the lives and works of Emil Kraepelin - often considered the founder of modern scientific psychiatry, his teacher Bernhard Gudden, and his anatomist colleague Franz Nissl. The book describes scientific findings together with the methods used; it explains why diagnoses were then (and are still now) so difficult to make; it also explores mind-brain controversies. The Making of Modern Psychiatry will inform and delight mental health professionals as well as all persons curious about the origins of modern psychiatry.